Influence of water storage time on the bond strength of etch-and-rinse and self-etching adhesive systems - Dantas,Darlene Cristina Ramos Eloy (2008)
The purpose of this study was to evaluate comparatively the shear bond strength (SBS) of etch-and-rinse (Adper Scotch Bond Multi Purpose - ASBMP and Adper Single Bond 2 - ASB2) and self-etching (AdheSe -AD and Adper Prompt - AP) adhesive systems after short- and long-term water storage. Eighty bovine teeth were randomly assigned to 4 groups (n=20, 10 teeth for 24 h and 10 for 6 months). After surface treatment, composite resin cylinders were made with Tetric Ceram using a bisected metallic matrix. The specimens were stored in distilled water at 37°C for either 24 h or 6 months. After these periods, shear strength was assessed in a universal testing machine (0.5 mm/min). Data were submitted to ANOVA and F test at 5% significance level. Mean SBSs (MPa) for ASBMP (10.03 ± 3.78) and ASB2 (6.10 ± 2.67) showed no statistically significant differences (p>0.05) between times. The self-etching systems did not differ significantly from each other within the 24-h period, but significant difference was found for AD (1.37 ± 0.64) after 6 months of water storage. In conclusion, the tested etch-and-rinse systems had a better performance in terms of bond durability over time than the self-etching systems.